2019
DOI: 10.3389/fimmu.2018.03076
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Induces Neutrophil Extracellular Traps Formation Through an NADPH Oxidase-Dependent Pathway in Diabetic Retinopathy

Abstract: Neutrophil extracellular traps (NETs), the product of NETosis, is found to localize pathogens and crystals in immune response. Recent studies have found that excessive NETs lead to disease conditions such as diabetes and its complications like diabetic retinopathy (DR). However, the correlation between NETs and high glucose or DR remains unclear. Here, we found NETs level was significantly increased in the serum of diabetic patients, especially in proliferation diabetic retinopathy (PDR) patients. High glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(144 citation statements)
references
References 40 publications
3
113
1
3
Order By: Relevance
“…In a case-control association study, dsDNA-histone complex and NE levels were significantly increased in patients with diabetic retinopathy compared with those without [55]. As a further proof of it, Wang et al reported that an increased NET formation was observed in the serum of T2D patients with diabetic retinopathy irrespective of the stage of the disease, with NE driving this trend [59].…”
Section: Nets In Diabetesmentioning
confidence: 92%
See 1 more Smart Citation
“…In a case-control association study, dsDNA-histone complex and NE levels were significantly increased in patients with diabetic retinopathy compared with those without [55]. As a further proof of it, Wang et al reported that an increased NET formation was observed in the serum of T2D patients with diabetic retinopathy irrespective of the stage of the disease, with NE driving this trend [59].…”
Section: Nets In Diabetesmentioning
confidence: 92%
“…As NET formation is likely to be associated with glucose-stimulated reactive oxygen species (ROS) production, it is possible that ROS have a direct effect on NET production. In fact, diphenyleneiodonium and apocynin, two inhibitors of NADPH oxidase, reduce NET formation in neutrophils exposed to high glucose stimulation [59]. Accordingly, the inhibition of NADPH oxidase markedly decreased the release of extracellular DNA compared to high glucose condition, thus suggesting that glucose-induced NET production might be dependent on NADPH oxidase [59].…”
Section: Nets In Diabetesmentioning
confidence: 96%
“…Besides, Nemeth et al showed by ELISA and reverse transcription quantitative PCR (RT-qPCR) increased levels of HNP1–3 in the plasma of T1D patients; however, similar increases were observed in type 2 diabetes (T2D) patients, suggesting that hyperglycemia may be responsible for such increases and, consequently, may only be a consequence of the disease and not a cause ( 82 ). Indeed, hyperglycemia was demonstrated in a diabetic rat model to promote NET formation ( 83 ). Importantly, these studies measured the circulating levels of AMPs in patients that may not reflect the levels in the pancreas.…”
Section: The Role Of Amps In Autoimmune Diseasementioning
confidence: 99%
“…Recently, Barnes et al suggested that COVID‐19, 8 just like hyperglycaemia, 9 might induce abnormal production of neutrophil extracellular traps (NETs). NETosis is a neutrophil‐specific strategy to kill extracellular pathogens, consisting in the release of a decondensed chromatin web beaded with granular antimicrobial enzymes 9 .…”
Section: Figurementioning
confidence: 99%